Cote d'Ivoire : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2009)
Cote d'Ivoire's request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility is discussed. Cote d'Ivoire is making progress toward reunification, peace, and elections. Cote d'Ivoire's economy has been resilient to the global downturn, but there are indications of a slowdown in certain economic activities, such as mining investment and nontraditional exports. The authorities took remedial measures to partly offset the extrabudgetary spending and put in place safeguards against such spending while ensuring full transparency of investment spending and oil revenue.